(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
This article seeks to study the phenomenon of violence and its impact on the psychological structure of the central character in the novel Space for Madness by the Iraqi writer Saad Muhammad Rahim. Standing on its types and causes, and on violence and its existence as a phenomenon in the novel (Space for Madness) in a very intensive manner, then the study moves to the analysis that deals with examples from the novel that include stations in the life of the protagonist, depicting violence. The focus was on the most prominent types; Physical, psychological, verbal, and sexual violence (rape) to be analyzed, studied, and its impact on the central character clarified. Then the study ends with a conclusion that includes the most important results that I drew from tracking the events of the novel, which are related to the phenomenon of violence, then a list of sources and references.